Analisis Hubungan Faktor Family Resource dan Faktor Community Resource Dengan Pemanfaatan Pelayanan Neonatal di Wilayah Kerja Puskesmas X Surabaya - SAIFULLAH, MUCHAMAD DAFFA; Atho’illah, M. Arju Ilmi; Damayanti, Nyoman Anita (Media Gizi Kesmas, 2025)
Background: Infant mortality is one of the priority problems in the field of maternal and child health in Indonesia until now. All health issues in the Sustainable Development Goals (SDG's) are integrated into goal number 3. In the city of Surabaya, the total number of infant deaths has shown a decreased trend in the last 3 years, but in the number of infant deaths, including deaths within the neonatal period, the number continued to increase during 2018-2020. The target of neonatal visits in the working area of Puskesmas X Surabaya is one of the causes of the infant mortality rate during the neonatal period in the city of Surabaya having increased in 2018-2019, especially in the working area of Puskesmas X Surabaya which makes the Puskesmas rank second in the number of neonatal deaths in Surabaya in 2019. Objectives: To analyze factors related to the use of neonatal services in the working area of Puskesmas X Surabaya. Methods: This type of research was an analytical observational study with a quantitative approach. The design of this research used cross-sectional studies. The sampling technique used in this study was probability sampling. Results: From the research conducted, it was shown that there was no significant relationship between family resource and community resource with the use of neonatal services by  mothers of infants, judging from statistical tests using the Chi-square test, the p-value obtained was more than α=0,05. Conclusions: The enabling characteristics of the baby's mother, such as insurance ownership, family income, husband support, family support, health worker support, and accessibility, were not related to the use of neonatal services by the baby's mother in the work area of Puskesmas X Surabaya.